DIPLOMASI EKONOMI PEMERINTAH KANADA DALAM NEGOSIASI SEKTOR AGRIKULTUR CETA (CANADA – EUROPEAN UNION COMPREHENSIVE ECONOMIC TRADE AGREEMENT) - Nurlaila, Siti Meisa; Fasisaka, Idin; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2019)
ABSTRACT The cooperation between Canada and European Union started on 2009 is named as CETA. The reason why CETA is carried out by Canada is to reduce dependence on the United States. However, during the negotiation, Canada faces an obstacles on the agriculture sector. The opening of the Canadian market by increasing the cheese import quota is considered to be harmful to local cheese producers and violates the supply management system that protects the local dairy sector since 1970. This research analyzes economic diplomacy and two-level negotiations (international and domestic) Canada does in 2009 until 2017. The concepts used in this research are economic diplomacy concept and two-level games theory. Research data is obtained from various sources, such as books, journals, scientific research, and reports related to this study. Keywords: CETA, Two-Level Games Theory, Economic Diplomacy, Agriculture Sector